The study of inhibiting structural material corrosion in water recycling systems by sodium hydroxide - Pilipenko, Alexei; Pancheva, H.; Reznichenko, G.; Mirgorod, O.; Miroshnichenko, N.; Sincheskul, A. (Технологический центр, 2017)
Influence of sodium hydroxide on the rate and nature of corrosion of St3 carbon steel and SCh 18-36 grey cast iron in highly mineralized recycling water was studied. The nature of the corrosion damage was determined and the weight index of corrosion of these alloys was calculated. By means of polarization measurements, the electrochemical indices of anodic processes on steel and cast iron were determined. The effect of the circulating water pH on behavior of steel and cast iron under anodic polarization has been studied by cyclic voltammetry. It has been shown that the effective impact of pH on characteristics of the anode processes occured at pH≥11.4. At these pH values, the metal steady-state potential shifted to a region of positive values which was an indication of inhibition of the anodic process itself. At pH≥11.4, the pitting potential significantly shifted to the positive side: the process of healing pits was faster than their formation. It has been established that steel and especially cast iron tend to pass into a passive state at pH> 10. The corrosion rate values did not exceed this index for the studied alloys in distilled water and were in the range of acceptable values. Thus, it is possible to effectively inhibit the rate of steel and cast iron corrosion, especially in the waterline zone by shifting the pH of the circulating water to the alkaline region. As a result of the conducted studies, optimal working conditions for iron alloys as the most technically important structural materials for designing closed cycles of circulating water supply systems have been established.
Keywords: circulating water; corrosion; carbon steel; grey cast iron; mineralization; sodium hydroxide